TRANSFORMASI METODE PENELITIAN ILMIAH MELALUI PENDEKATAN FILSAFAT ILMU - ASMIATI; SIMINTO; YATIN MUYONO (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article examines the transformation of scientific research methods influenced by the development of the philosophy of science throughout history. The philosophy of science serves as an epistemological foundation that determines how researchers perceive reality, truth, and verification procedures. Through a systematic literature review, this article explores how schools of the philosophy of science — ranging from positivism, post-positivism, constructivism, to pragmatism — have shaped the paradigms of quantitative, qualitative, and mixed-method research. The findings indicate that the transformation of research methodology is not merely a technical change, but rather a fundamental shift in the way scientists construct meaning from knowledge. A philosophical approach to science provides a critical framework for researchers to select appropriate methods, identify ontological and epistemological assumptions, and integrate diverse perspectives in order to produce more comprehensive and relevant knowledge. This article is intended to serve as a meaningful contribution to the development of research methodology in Indonesia, particularly within the context of the social sciences and humanities.